Language Complexities of Communication in the Age of Post-Humanism - Sotanasathien, Surapongse (Journal of Posthumanism, 2025)
This topic describes language complexities due to influences of disruptive innovations and impacts linguistics in structures and functions of changing language. As a result, their trends disturb societal language because of a battle between human intelligence and artificial intelligence to find out a solution for a society and culture through posthumanism language. The implications of AI-driven algorithmic innovations are leading to transcribe amongst non-verbal language, verbal language, and semantic communication across languages at prompt.